The Importance of the Tax System for the Rule of Law. The Dutch Childcare Allowance Scandal as an Example of a Violation of the Rule of Law in a Constitutional Democracy - Essers, Peter (Challenges of Contemporary Tax Law: Jubilee Book Dedicated to Professor Włodzimierz Nykiel. Volume II, 2024)
If a tax system does not respect the rule of law and the government acts as an omnipotent ruler, innocent citizens will be the first victims as they are not in an equal position with the bureaucrats representing this government. This can even happen in modern states that embrace the modern principles of democracy and the rule of law. In this contribution this is illustrated with a recent example in the Netherlands with respect to the system of childcare allowances for parents. This system, executed by the Dutch tax administration, has brought about 26,000 parents into huge problems since they had to pay back large sums of received allowances because of presumed offences. This not only led to big financial problems for these parents, combined with seizures, also all kinds of personal problems like divorces and illnesses resulted from this. As turned out later, most of these parents had been wrongly accused. Because the executive tax officers had to follow the wording of the law, there was no place for a policy of leniency. As a result, the least imperfection on the part of the parents in applying for the childcare allowances led to the obligation to pay back the full amount of these allowances received in advance (the “all or nothing” policy). In 2021, the Dutch government resigned because of this scandal.